Do measures of reactive balance control predict falls in people with stroke returning to the community?. Issue 4 (December 2015) - Mansfield, A.; Wong, J.S.; McIlroy, W.E.; Biasin, L.; Brunton, K.; Bayley, M.; Inness, E.L.
Abstract: Objective: To determine if reactive balance control measures predict falls after discharge from stroke rehabilitation. Design: Prospective cohort study. Setting: Rehabilitation hospital and community. Participants: Independently ambulatory individuals with stroke who were discharged home after inpatient rehabilitation ( n = 95). Main outcome measures: Balance and gait measures were obtained from a clinical assessment at discharge from inpatient stroke rehabilitation. Measures of reactive balance control were obtained: (1) during quiet standing; (2) when walking; and (3) in response to large postural perturbations. Participants reported falls and activity levels up to 6 months post-discharge. Logistic and Poisson regressions were used to identify measures of reactive balance control that were related to falls post-discharge. Results: Decreased paretic limb contribution to standing balance control [rate ratio 0.8, 95% confidence interval (CI) 0.7 to 1.0; P = 0.011], reduced between-limb synchronisation of quiet standing balance control (rate ratio 0.9, 95% CI 0.8 to 0.9; P < 0.0001), increased step length variability (rate ratio 1.4, 95% CI 1.2 to 1.7; P = 0.0011) and inability to step with the blocked limb (rate ratio 1.2, 95% CI 1.0 to 1.3; P = 0.013) were significantly associated with increased fall rates when controlling for age, stroke severity, functional balance and daily walking activity. Conclusions: Impaired reactive balance control in standing and walking predicted increased risk of falls post-discharge from stroke rehabilitation. Specifically, measures that revealed the capacity of both limbs to respond to instability were related to increased risk of falls. These results suggest that post-stroke rehabilitation strategies for falls prevention should train responses to instability, and focus on remediating dyscontrol in the more-affected limb.